Antiretroviral Therapy Initiation Following Policy Changes: Observations From China. (July 2016) - Li, Li; Ji, Guoping; Lin, Chunqing; Liang, Li-Jung; Lan, Chiao-Wen
China's HIV/AIDS treatment policies have been evolving over the preceding decade. This study describes patterns of antiretroviral therapy (ART) initiation for a sample of people living with HIV/AIDS (PLHIV) in rural Anhui, China, where most PLHIV were infected via paid plasma donation during the 1990s. A total of 481 PLHIV who were receiving ART were included in our analyses. Times between HIV diagnosis and the initiation of ART were examined relative to the time points when major ART-related policies changed in China. More than half (53%) of PLHIV who had been diagnosed by 2003 received ART within 6 months, whereas 93% of PLHIV who had been diagnosed in 2010 or later received ART within 6 months. The study results provide additional support that the "Four Frees and One Care" policy in 2003 and the relaxation of ART eligibility in 2010 have facilitated the initiation of treatment for PLHIV in China.